Evaluation of a Portable Automated Serum Chemistry Analyzer for Field Assessment of Harlequin Ducks, Histrionicus histrionicus - Michael K. Stoskopf; Daniel M. Mulcahy; Daniel Esler (Veterinary Medicine International)
A portable analytical chemistry analyzer was used to make field assessments of wild harlequin ducks (Histrionicus histrionicus) in association with telemetry studies of winter survival in Prince William Sound, Alaska. We compared serum chemistry results obtained on-site with results from a traditional laboratory. Particular attention was paid to serum glucose and potassium concentrations as potential indicators of high-risk surgical candidates based on evaluation of the field data. The median differential for glucose values (N=82) between methods was 0.6 mmol/L (quartiles 0.3 and 0.9 mmol/L) with the median value higher when assayed on site. Analysis of potassium on site returned a median of 2.7 mmol/L (N=88 ; quartiles 2.4 and 3.0 mmol/L). Serum potassium values were too low for quantitation by the traditional laboratory. Changes in several serum chemistry values following a three-day storm during the study support the value of on site evaluation of serum potassium to identify presurgical patients with increased anesthetic risk.